Electrode kinetics from a single experiment: multi-amplitude analysis in square-wave chronoamperometry - Guziejewski, Dariusz; Stojanov, Leon; Zwierzak, Zuzanna; Compton, Richard G; Mirceski, Valentin (Royal Society of Chemistry (RSC), 2022)
The recently introduced technique of square-wave chronoamperometry (SWCA) is studied under conditions of progressively increasing height of potential pulses (square-wave amplitude) within a single experiment. In multi-amplitude square-wave chronoamperometry (MA-SWCA) a potential modulation consisting of square-wave forward and reverse potential pulses is imposed on a constant mid-potential; the amplitude of pulses increases progressively during the experiment. This allows the fast and reliable estimation of kinetic parameters at a constant pulse frequency in a single experiment, based on the resulting feature known as the amplitude-based quasireversible maximum. The proposed methodology is tested by simulating the responses of a simple quasireversible electrode reaction of a dissolved redox couple and a surface confined electrode reaction. Compared with conventional square-wave voltammetry (SWV) and SWCA, MA-SWCA shows advantages in estimation of the standard rate constant in terms of simplicity, speed and efficiency for both studied electrode mechanisms.